Third molar extraction and its complications: literature review (Research, Society and Development, 2021)
Third molar extraction is a dental practice with a potential risk of causing complications. Therefore, it is necessary to carry out an adequate planning to prevent transoperative accidents and postoperative complications, since although surgeries are scheduled and performed by specialized and trained professionals, they are not free from complications. Nineteen studies indexed in the BVS, Lilacs, Scielo and Pubmed databases were selected. The selection of articles took place according to the inclusion and exclusion criteria. The full reading of the papers was the basis for writing the review. Given the above third molar exeresis implies complications such as alveolitis, hemorrhages, nerve injuries and fractures. Although well described in the literature, fortunately, they are not routine, but they do exist. Therefore, it is inferred the importance of knowledge and mastery of the subject, both for acting in prevention and for handling the situation.